PEMANFAATAN TEKNOLOGI ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN MODERASI BERAGAMA - Ummi Kulsum; Wiasih; Abdul Khalik; Ifada Retno Ekaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The rapid development of Artificial Intelligence (AI) technology has brought significant transformation to the educational sector, including efforts to strengthen religious moderation in the digital era. This study aims to analyze the utilization of Artificial Intelligence in religious moderation education, identify its opportunities and challenges, and formulate an AI-based educational model that supports the reinforcement of religious moderation values. This research employs a qualitative approach using a library research method. Data were collected from various sources, including books, national and international scientific journals, research articles, policy documents, and relevant literature related to Artificial Intelligence, Islamic education, and religious moderation. Data analysis was conducted through content analysis involving identification, classification, interpretation, and conceptual synthesis. The findings reveal that Artificial Intelligence has significant potential to support religious moderation education through personalized learning, virtual tutoring systems, digital religious literacy enhancement, adaptive learning resources, and early detection of intolerant, radical, and misleading religious content. The utilization of AI can also improve the accessibility, effectiveness, and quality of religious moderation learning in accordance with the characteristics of the digital generation. However, its implementation faces several challenges, including algorithmic bias, contextual limitations, technological dependency, and issues related to ethics and data privacy. Therefore, the integration of AI in religious moderation education should be implemented comprehensively while maintaining the central role of teachers as facilitators in the internalization of religious values. This study proposes an integrative model of AI utilization that combines digital technology, religious literacy, and moderation-based education to foster a generation that is tolerant, inclusive, critical, and committed to harmonious religious life within a multicultural society.